2022
DOI: 10.30656/jak.v9i1.4060
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Corporate Governance Terhadap Kualitas Sustainability Reporting

Abstract: Laporan keberlanjutan merupakan bagian penting dari penilaian kinerja perusahaan. Studi ini dilakukan untuk memenuhi kajian atas pengaruh dari tata kelola perusahaan terhadap kualitas laporan keberlanjutan dengan indeks laporan keberlanjutan menggunakan six point scale yang dilatarbelakangi oleh perbedaan pemikiran dari peneliti sebelumnya. Penelitian ini menggunakan model regresi linear berganda yang akan dilakukan pada 232 perusahaan non-financial yang terdaftar pada Bursa Efek Indonesia. Penentuan sampel da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
0
5
0
5
Order By: Relevance
“…The following operational variables were used in this study: This Sustainability Report Disclosure variable is calculated using GRI indicators that are listed in the sustainability report disclosure index (SRDI). Giving a score of 1 if the item is revealed and a score of 0 if the item is not revealed, then dividing by 91 (Purbandari and Suryani, 2018). The formula for calculating the sustainability report is as follows: To measure the implementation of activities carried out by the board of directors to support corporate governance, the number of meetings between members of the board of directors will be calculated over a one-year period (Oktaviani dan Amanah, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following operational variables were used in this study: This Sustainability Report Disclosure variable is calculated using GRI indicators that are listed in the sustainability report disclosure index (SRDI). Giving a score of 1 if the item is revealed and a score of 0 if the item is not revealed, then dividing by 91 (Purbandari and Suryani, 2018). The formula for calculating the sustainability report is as follows: To measure the implementation of activities carried out by the board of directors to support corporate governance, the number of meetings between members of the board of directors will be calculated over a one-year period (Oktaviani dan Amanah, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…This is consistent with studies conducted by Dewi and Ramantha (2021), Krisyadi and Elleen (2020), and (Latifah dkk, 2019), which found that the board of directors had an impact on the sustainability report disclosure. Purbandari and Suryani (2018) found that the board of directors had no impact on the sustainability report's disclosure. This is due to the focus of the work of directors on the company's financial performance.…”
Section: Introductionmentioning
confidence: 96%
“…Companies that do not yet realize the importance of sustainability reports can be linked to good corporate governance. The role of GCG itself is important for long-term business continuity (Ekaputri & Eriandani, 2022).…”
Section: Picture 1 Disclosure Intensity Of Imperishable Reportmentioning
confidence: 99%
“…To increase shareholder confidence and improve business' reputation in the communal view that the company does not only focus on maximizing profits, it is necessary to disclose a sustainability report. On the other hand, sustainability reports can be used as a reference by other stakeholders (such as the government and others) to assess a company's commitment to sustainable development (Ekaputri & Eriandani, 2022).…”
Section: Picture 1 Disclosure Intensity Of Imperishable Reportmentioning
confidence: 99%
“…Research ini menunjukan hasil yang sama dengan penelitian (Madona & Khafid, 2020) dan (Ekaputri & Eriandani, 2022) yaitu Board Independence berpengaruh negatif terhadap pengungkapan Sustainable Reporting, sehingga menghasilkan kontribusi penelitian dimana entitas yang menjalankan prinsip good corporate governance pastinya akan mengungkapkan tanggung jawab sosial untuk kepentingan para pemangku kepentingan. Dikarenakan kelangsungan hidup entitas sangat tergantung pada tingkat kepercayaan dari para stakeholder terhadap Sustainable Reporting, dengan demikian tidak sesuai dengan teori stakeholder yang dimana entitas dapat memenuhi harapan dan kepentingan stakeholder, seperti penyediaan informasi Sustainable Reporting.…”
Section: Uji Signifikansi Parameter Individual (Uji Statistik T)unclassified